Long‐Term Outcomes of Cardiac Resynchronization Therapy Using Apical Versus Nonapical Left Ventricular Pacing - Francisco Leyva; Abbasin Zegard; Robin J. Taylor; Paul W. X. Foley; Fraz Umar; Kiran Patel; Jonathan Panting; Peter van Dam; Frits W. Prinzen; Howard Marshall; Tian Qiu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background Experimental evidence indicates that left ventricular (LV) apical pacing is hemodynamically superior to nonapical LV pacing. Some studies have shown that an LV apical lead position is unfavorable in cardiac resynchronization therapy. We sought to determine whether an apical LV lead position influences cardiac mortality after cardiac resynchronization therapy. Methods and Results In this retrospective observational study, the primary end point of cardiac mortality was assessed in relation to longitudinal (basal, midventricular, or apical) and circumferential (anterior, lateral, or posterior) LV lead positions, as well as right ventricular (apical or septal), assigned using fluoroscopy. Lead positions were assessed in 1189 patients undergoing cardiac resynchronization therapy implantation over 15 years. After a median follow‐up of 6.0 years (interquartile range: 4.4–7.7 years), an apical LV lead position was associated with lower cardiac mortality than a nonapical position (adjusted hazard ratio: 0.74; 95% confidence interval, 0.56–0.99) after covariate adjustment. There were no differences in total mortality or heart failure hospitalization. Death from pump failure was lower with apical than nonapical positions (adjusted hazard ratio: 0.69; 95% confidence interval, 0.51–0.94). Compared with a basal position, an apical LV position was also associated with lower risk of sudden cardiac death (adjusted hazard ratio: 0.34; 95% confidence interval, 0.13–0.93). No differences emerged between circumferential LV lead positions or right ventricular positions with respect to any end point. Conclusions In recipients of cardiac resynchronization therapy, an apical LV lead position was associated with better long‐term cardiac survival than a nonapical position. This effect was due to a lower risk of pump failure and sudden cardiac death.